Are we ready to treat hepatitis C virus in individuals with opioid use disorder: assessment of readiness in European countries on the basis of an expert-generated model. Issue 11 (November 2017) - Wright, Nat; Reimer, Jens; Somaini, Lorenzo; Roncero, Carlos; Maremmani, Icro; Simon, Nicolas; Krajci, Peter; Littlewood, Richard; D'Agnone, Oscar; Alho, Hannu; Rolland, Benjamin
Abstract : Individuals with a history of injecting drugs have a high prevalence of chronic hepatitis C (HCV) infection. Many have a history of opioid use disorder (OUD). Despite novel treatments with improved efficacy and tolerability, treatment is limited in the group. A faculty of experts shared insights from clinical practice to develop an HCV care-readiness model. Evidence and expert knowledge was collected. Ten experts developed a model of three factors (with measures): 'healthcare engagement', 'guidance' and 'place'. Overall, 40–90% of individuals with OUD engage with drug treatment services. Ten of 12 HCV guidelines provided specific advice for the OUD population. Ten of 12 OUD care guidelines provided useful HCV care advice. In 11 of 12 cases, location of HCV/drug treatment care was in different places. This readiness assessment shows that there are important limitations to successful HCV care in OUD. Specific actions should be taken: maintain/increase access to OUD treatment services/opioid agonist therapy, updating HCV guidance, locate care in the same place and allow wider prescribing of anti HCV medicines.